2022
DOI: 10.1007/s12032-022-01655-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on human bone-derived mesenchymal stromal cell—breast cancer cell line interactions

Abstract: Metformin is used to treat patients with type 2 diabetes mellitus and was found to lower the incidence of cancer. Bone metastasis is a common impairment associated with advanced breast cancer. The present study investigated the effects of metformin on human bone-derived mesenchymal stromal cells (BM-MSC)—breast cancer cell line interactions. BM-MSCs grown from box chisels were tested for growth-stimulating and migration-controlling activity on four breast cancer cell lines either untreated or after pretreatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The good one is associated with apoptisis, and the bad one is related to treatment resistance ( 12 , 111 , 144 , 171 , 178 ). As vaccines, lentiviral vectors, non-anticancer drugs and biological extracts were found to have positive implications for cellular compositions changes in the TME, we see the benefits of combination administration targeted cellular compositions of the TME and other conventional treatments in BC ( 187 , 191 , 193 , 197 ). The cellular compositions of the TME and and therapeutic mechanisms deserves further study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The good one is associated with apoptisis, and the bad one is related to treatment resistance ( 12 , 111 , 144 , 171 , 178 ). As vaccines, lentiviral vectors, non-anticancer drugs and biological extracts were found to have positive implications for cellular compositions changes in the TME, we see the benefits of combination administration targeted cellular compositions of the TME and other conventional treatments in BC ( 187 , 191 , 193 , 197 ). The cellular compositions of the TME and and therapeutic mechanisms deserves further study.…”
Section: Discussionmentioning
confidence: 93%
“…Metformin is used to treat patients with type 2 diabetes and has recently been found to reduce the incidence of cancer. Teufelsbauer et al reported that, when treated with metformin, MSCs preferentially differentiate into the osteogenic lineage, thus releasing factors that inhibit the migration of breast cancer cells (191). The exosomal CXCR4 + TRAIL is transduced from MSCs via a lentiviral vector.…”
Section: Targeting the Cellular Composition Of The Tumor Microenviron...mentioning
confidence: 99%
“…Metformin, an organic compound, is a first-line drug for treatment of type 2 diabetes. Metformin has been widely studied for its anticancer, anti-inflammatory and osteogenic effects [ 158 , 159 ]. Tan et al successfully developed the poly (L-lactic ac-id)/n-HAp/metformin (PLLA/n-HAp/MET) nanocomposite scaffold using SLS technology.…”
Section: Drug-loaded N-hap Composite Scaffoldsmentioning
confidence: 99%